Case of primary retroperitoneal hydatid - Khwaunju, P; Tamrakar, K K; Sah, K; Neupane, H C (Journal of Chitwan Medical College, 2017)
Hydatid disease is a common condition usually involving liver and lungs. Primary retroperitoneal hydatid is not a common occurrence and it may mimic other retroperitoneal tumors clinically and radiologically. We herein present a case of primary retroperitoneal hydatid mimicking retroperitoneal mass. It was diagnosed by CT scan and FNAC examinations and managed surgically.